Peranan Belajar Mengajar Berbasis Teknologi Informasi dalam Meningkatkan Mutu Pembelajaran - Putri Maya Lestari; Bukman Lian; Mulyadi Mulyadi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The purpose of this study is to describe and analyze solutions in the role of information technology-based teaching and learning in improving the quality of learning at SDN 3 Koba Bangka Tengah. This research was conducted at SDN 3 Koba Bangka Tengah, Bangka Belitung Islands Province. The research period was from June to September 2024. The object of this study was the entire learning process that utilizes information technology as a means and media to support teaching and learning activities. This study used a qualitative descriptive method. The data sources used consisted of primary data obtained through direct observation in the classroom and interviews with teachers, principals, and students; and secondary data in the form of learning administration documents, teaching tools, and learning outcome reports. Data collection techniques included participatory observation, in-depth interviews, and documentation studies. Data validity was tested by triangulation of sources to ensure the accuracy and consistency of information. The results showed that the use of information technology, such as the use of projectors, learning videos, and digital-based educational applications, significantly helped improve student motivation and understanding of the material. In addition, teachers showed quite good adaptation in using technological devices to support the learning process. However, several obstacles remain, such as limited internet network facilities, a lack of technology training for teachers, and inadequate school infrastructure. Nevertheless, the implementation of information technology has been proven to improve the quality of learning when supported by visionary school policies, ongoing teacher training, and active parental involvement in students' learning processes. These findings reinforce the importance of technology integration as a 21st-century learning strategy. Overall, information technology-based learning is an innovative solution for creating a more interactive, effective, and relevant learning environment.